Analisis Antara Bauran Pemasaran, Mutu Pelayanan dan Referensi dengan Keputusan Pasien Memilih Kembali Jasa Pelayanan di Klinik Pratama Rawat Inap Shofa Gondangrejo Karanganyar Jawa Tengah - Habibi, Novel; Paramata, Vip; Asnar, Etty Sofia Mariati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The 24.33% decrease in the number of patients at the Shofa Inpatient Primary Clinic from 2021 to 2022 was caused by competition between private clinics and complaints about services. To overcome this, the clinic carries out analysis related to decision making regarding service use, with a focus on marketing mix, service quality and referrals. This quantitative descriptive research involved 13,000 outpatient service users between January-April 2023, with a sample of 207 people aged 20 to 64 years. Data was collected using a Likert scale questionnaire and analyzed using descriptive analysis and multiple linear regression tests. The research results show positive perceptions of the marketing mix and service quality, as well as high references to the clinic. Most respondents stated that they would return to using clinic services. Research shows that the marketing mix influences the decision to return to using health services, and service quality has a positive influence. However, references did not have a significant influence on the decision. Simultaneously, the marketing mix, service quality and references contributed 78.6% to the decision to return to using the service. The service quality variable has the greatest influence (t count 19.612). Suggestions for clinics are to improve the marketing mix, provide clear service quality standards, and ensure that health workers show more empathy and attention to consumer characteristics, so that they can encourage consumers' decisions to return to using health services.